The study of the level of awareness of pharmacists on vaccination against human papillomavirus and the role of pharmacists in the prevention of cervical cancer - Kotvitska, A. A.; Volkova, A. V.; Korzh, Iu. V.; Ovakimian, O. S.; Tereschenko, L. V.; Shabratska, D. E. (Social Pharmacy in Health Care, 2024)
Aim. To study the awareness of pharmacists about vaccination against human papillomavirus (HPV) and the role of pharmacists in the prevention of cervical cancer. Materials and methods. The results of a survey of pharmacists on vaccination against HPV and the role of pharmacists in the prevention of cervical cancer are presented. The data analysis is accompanied by the use of systematic, sociological (questionnaire survey) analysis, comparison and generalization. Results. A pharmacist plays an important role in providing information to the public about human papillomavirus, vaccination against human papillomavirus and the risk of cervical cancer. According to the results of the survey, it has been determined that the majority of respondents consider it appropriate for pharmacists to participate in programs that will help to raise public awareness about the human papillomavirus, the importance of HPV vaccination and the risk of cervical cancer. However, only about 20 % of doctors provide this information to their patients, while almost 80 % do not. Low information awareness of the population has been identified as a key factor affecting vaccination readiness. Conclusions. Based on the analysis, it has been found an insufficient level of knowledge about human papillomavirus among pharmacists to inform the population, as well as a lack of willingness to participate in activities aimed at raising public awareness about vaccination against papillomavirus.